2022
DOI: 10.32487/jtt.v10i2.1569
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Tahanan dan Biaya Material Kapal Perikanan Fiberglass Pada Perairan Kabupaten Buton Selatan

Abstract: Pembuatan kapal nelayan berbahan fiberglass saat ini sedang mengalami perkembangan yang besar. Beberapa faktor yang menjadi keunggulannya adalah karena biaya yang dikeluarkan lebih murah, bahan material yang digunakan kuat dan awet, serta material yang digunakan dapat dengan mudah dijangkau. Saat ini, beberapa pengrajin kapal kayu lebih memilih untuk membuat kapal berbahan fiberglass sehingga produksi tetap bisa dilakukan. Penelitian ini bertujuan untuk menentukan desain dan kapasitas kapal yang cocok digunaka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…According to several previous studies, the background to innovation in making fiberglass boats could be based on several weaknesses that wooden boats have, such as being vulnerable to brittleness and leaking; On the other hand, boats made from fiberglass are more leak-resistant, the life or service life of the (Mubarak, 2022). Corroborated by the results of other research, it is shown that with its high durability and high resistance to water, this fiberglass material is considered very suitable to be used as a supporting material for ship hull coatings.…”
Section: Introductionmentioning
confidence: 99%
“…According to several previous studies, the background to innovation in making fiberglass boats could be based on several weaknesses that wooden boats have, such as being vulnerable to brittleness and leaking; On the other hand, boats made from fiberglass are more leak-resistant, the life or service life of the (Mubarak, 2022). Corroborated by the results of other research, it is shown that with its high durability and high resistance to water, this fiberglass material is considered very suitable to be used as a supporting material for ship hull coatings.…”
Section: Introductionmentioning
confidence: 99%